2003
DOI: 10.1046/j.1471-4159.2003.02165.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of neutral sphingomyelinase produced ceramide in lipopolysaccharide‐mediated expression of inducible nitric oxide synthase

Abstract: Lipopolysaccharide (LPS) and interferon-c (IFN) treatment of C6 rat glioma cells increased the intracellular ceramide level and the expression of the inducible nitric oxide synthase (iNOS) gene. To delineate the possible role of ceramide in the induction of iNOS, we examined the source of intracellular ceramide and associated signal transduction pathway(s) with the use of inhibitors of intracellular ceramide generation. The inhibitor of neutral sphingomyelinase (3-O-methylsphingomyelin, MSM) inhibited the indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 69 publications
0
48
1
Order By: Relevance
“…LacCer is a precursor for complex GSLs, including gangliosides [3]. Previous studies have shown the involvement of sphingolipids such as ceramide and psychosine in the cytokine-mediated inflammatory disease of CNS, such as Krabbe disease and spinal cord injury [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…LacCer is a precursor for complex GSLs, including gangliosides [3]. Previous studies have shown the involvement of sphingolipids such as ceramide and psychosine in the cytokine-mediated inflammatory disease of CNS, such as Krabbe disease and spinal cord injury [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Although many reasons have been put forward to explain the obvious lack of CNS regeneration following injury/neurotrauma, the robust formation of the glial scar, as a result of astrogliosis, is also known to interfere with subsequent neural repair or axonal regeneration (2, 10). Thus, considerable effort is being directed toward understanding the mechanisms involved in astrocyte proliferation and reactivity in order to design therapeutic approaches to modulate gliosis, which is an impediment to neuronal recovery and axonal regeneration.Studies from our laboratory and others have shown the involvement of sphingolipids such as ceramide and psychosine in the potentiation of cytokine-mediated inflammatory disease (11)(12)(13)(14). In addition, we have recently reported the involvement of lactosylceramide in the regulation of inducible nitricoxide synthase gene expression and the efficacy of the glycosphingolipid biosynthesis inhibitor (PDMP) in attenuating spinal cord injury (SCI)-induced inflammatory disease, demonstrating significantly improved functional outcome post-SCI (15).…”
mentioning
confidence: 99%
“…Studies from our laboratory and others have shown the involvement of sphingolipids such as ceramide and psychosine in the potentiation of cytokine-mediated inflammatory disease (11)(12)(13)(14). In addition, we have recently reported the involvement of lactosylceramide in the regulation of inducible nitricoxide synthase gene expression and the efficacy of the glycosphingolipid biosynthesis inhibitor (PDMP) in attenuating spinal cord injury (SCI)-induced inflammatory disease, demonstrating significantly improved functional outcome post-SCI (15).…”
mentioning
confidence: 99%
“…Ceramideregulated NO production has been reported in vascular smooth muscle cells, astrocytes, microglias, macrophages, and C6 rat glioma cells after TNF-a and LPS/IFN-g stimulation (59,60). Expression of iNOS is required for NO production under inflammatory stimulation.…”
Section: Discussionmentioning
confidence: 99%